Security Assessment of Open-Source Village Governance Systems: A Case Study of OpenSID - Fanani, Ikhsan; Sujana, Nana; Susanta, Muhamad Hilmansyah (Progresif: Jurnal Ilmiah Komputer, 2026)
Indonesia's OpenSID platform manages sensitive citizen data across thousands of rural administrative units, yet no empirical security assessment exists in academic literature. This study addresses this gap through comprehensive security evaluation using Static Application Security Testing (SAST) and Software Composition Analysis (SCA), with findings mapped to OWASP Top 10 and scored using CVSS v3.1. Analysis identified 402 raw findings, with 170 (42.3%) confirmed as true positives after manual validation. Broken Access Control (105 findings) and Injection vulnerabilities (26 findings) were predominant, with seven Critical or High severity issues detected, including path traversal and known CVE dependencies. The 57.7% false positive rate emphasizes the necessity of manual validation alongside automated scanning. This research provides the first structured security audit of Indonesian governance software and recommends adopting GitHub-native security tools and formal vulnerability disclosure policies.Keywords: OpenSID; Security Assessment; OWASP Top 10; Static Application Security Testing; Village Information System  AbstrakPlatform OpenSID Indonesia mengelola data sensitif warga di ribuan unit administrasi pedesaan, namun belum ada penilaian keamanan empiris dalam literatur akademik. Penelitian ini mengisi kesenjangan tersebut melalui evaluasi keamanan komprehensif menggunakan Static Application Security Testing (SAST) dan Software Composition Analysis (SCA), dengan temuan dipetakan ke OWASP Top 10 dan dinilai menggunakan CVSS v3.1. Analisis mengidentifikasi 402 temuan mentah, dengan 170 (42,3%) dikonfirmasi sebagai true positive setelah validasi manual. Broken Access Control (105 temuan) dan kerentanan Injection (26 temuan) mendominasi, dengan tujuh masalah tingkat keparahan Critical atau High terdeteksi, termasuk path traversal dan dependensi CVE yang diketahui. Tingkat false positive 57,7% menekankan pentingnya validasi manual bersama pemindaian otomatis. Riset ini menyediakan audit keamanan terstruktur pertama untuk perangkat lunak tata kelola Indonesia dan merekomendasikan adopsi tools keamanan GitHub-native serta kebijakan pengungkapan kerentanan formal.Kata kunci: OpenSID; Asesmen Keamanan; OWASP Top 10; Static Application Security Testing; Sistem Informasi Desa